Mixed Fluorinated/Hydrogenated Self‐Assembled Monolayer‐Protected Gold Nanoparticles: In Silico and In Vitro Behavior. Issue 17 (3rd April 2019) - Marson, Domenico; Guida, Filomena; Şologan, Maria; Boccardo, Silvia; Pengo, Paolo; Perissinotto, Fabio; Iacuzzi, Valentina; Pellizzoni, Elena; Polizzi, Stefano; Casalis, Loredana; Pasquato, Lucia; Pacor, Sabrina; et al.
Abstract: Gold nanoparticles (AuNPs) covered with mixtures of immiscible ligands present potentially anisotropic surfaces that can modulate their interactions at complex nano–bio interfaces. Mixed, self‐assembled, monolayer (SAM)‐protected AuNPs, prepared with incompatible hydrocarbon and fluorocarbon amphiphilic ligands, are used here to probe the molecular basis of surface phase separation and disclose the role of fluorinated ligands on the interaction with lipid model membranes and cells, by integrating in silico and experimental approaches. These results indicate that the presence of fluorinated amphiphilic ligands enhances the membrane binding ability and cellular uptake of gold nanoparticles with respect to those coated only with hydrogenated amphiphilic ligands. For mixed monolayers, computational results suggest that ligand phase separation occurs on the gold surface, and the resulting anisotropy affects the number of contacts and adhesion energies with a membrane bilayer. This reflects in a diverse membrane interaction for NPs with different surface morphologies, as determined by surface plasmon resonance, as well as differential effects on cells, as observed by flow cytometry and confocal microscopy. Overall, limited changes in monolayer features can significantly affect NP surface interfacial properties, which, in turn, affect the interaction of SAM‐AuNPs with cellular membranes and subsequent effects on cells. Abstract : The structure that matters. Patterning of gold nanoparticles due to self‐assembling monolayers of amphiphilic immiscible ligands determines their behavior at the nano–bio interface.